Paradoxical reactions and immune reconstitution inflammatory syndrome in tuberculosis. (March 2015) - Bell, Lucy C.K.; Breen, Ronan; Miller, Robert F.; Noursadeghi, Mahdad; Lipman, Marc
Highlights: Case definitions for paradoxical reactions and immune reconstitution inflammatory syndrome (IRIS) in tuberculosis (TB) are reviewed. The risk factors and immunopathogenesis of these conditions are explored. Pathogenesis is discussed in the context of recent advances in TB research. A hypothesis is proposed for their core underlying pathogenesis. Summary: The coalescence of the HIV-1 and tuberculosis (TB) epidemics in Sub-Saharan Africa has had a significant and negative impact on global health. The availability of effective antimicrobial treatment for both HIV-1 (in the form of highly active antiretroviral therapy (HAART)) and TB (with antimycobacterial agents) has the potential to mitigate the associated morbidity and mortality. However, the use of both HAART and antimycobacterial therapy is associated with the development of inflammatory paradoxical syndromes after commencement of therapy. These include paradoxical reactions (PR) and immune reconstitution inflammatory syndromes (IRIS), conditions that complicate mycobacterial disease in HIV seronegative and seropositive individuals. Here, we discuss case definitions for PR and IRIS, and explore how advances in identifying the risk factors and immunopathogenesis of these conditions informs our understanding of their shared underlying pathogenesis. We propose that both PR and IRIS are characterized by the triggering of exaggerated inflammation in a setting of immunocompromise and antigen loading, via the reversal of immunosuppression by HAART and/or antimycobacterials. Further understanding of the molecular basis of this pathogenesis may pave the way for effective immunotherapies for the treatment of PR and IRIS.